ОСОБЕННОСТИ ЭМПАТИИ ПОДРОСТКОВ В НЕПОЛНЫХ СЕМЬЯХ / EMPATHY CHARACTERISTICS OF ADOLESCENTS IN INCOMPLETE FAMILIES - Stepanyan, Narine; Simonyan, Mariam (Bulletin of the Medical Institute after Mehrabyan, 2024)
Сегодня в нашем обществе большое внимание уделяется изучению возрастных особенностей подросткового возраста, особенно в отношении эмоциональной сферы. Исследования возрастной периодизации подросткового возраста в разные периоды практически всегда оставались актуальными, так как он характеризуется как бурный, нестабильный период, когда дети считают себя непонятыми, отвергнутыми, проигнорированными или нелюбимыми, из-за наличия высокого уровня негативизма наблюдаются эмоциональные и поведенческие нарушения, и это вызывает большую обеспокоенность родителей. В статье освещаются проявления эмпатии, обусловленные особенностями эмоциональной сферы подростков, особенно креативностью и склонностью к риску, которые тесно связаны со здоровым развитием эмоциональной сферы. Сегодня большое значение придается изучению особенностей проявления эмпатии, так как это, пожалуй, одна из актуальных проблем. Несмотря на значительное количество исследований эмпатии, ее изучение у подростков еще требует изучения, и можно сказать, что понимание развития эмпатии не является полным и системным. / Today, in our society, much attention is attracted to the study of the age characteristics of adolescence, especially in relation to the emotional sphere. Studies of the age periodization of adolescence in different periods have almost always remained relevant, since it is characterized as a turbulent, unstable period when children consider themselves misunderstood, rejected, ig-nored or unloved, due to the presence of a high level of negativism, emotional and behavioral disorders are observed, and this causes more concern for parents. The article highlights the manifestations of empathy caused by the peculiarities of the emotional sphere of adolescents, especially creativity and risk-taking, which are closely related to the healthy development of the emotional sphere. Today, great importance is attached to the study of the features of the manifestation of empathy, since this is, perhaps, one of the urgent problems. Despite the significant amount of research on empathy, its study in adolescents still requires further study, and it can be said that the understanding of the development of empathy is not complete and systematic.